2016
DOI: 10.1160/th15-09-0710
|View full text |Cite
|
Sign up to set email alerts
|

Phosphotidylserine exposure and neutrophil extracellular traps enhance procoagulant activity in patients with inflammatory bowel disease

Abstract: Inflammatory bowel disease (IBD)-associated thromboembolic event often lacks precise aetiology. The aim of this study was to investigate the contribution of phosphatidylserine (PS) exposure and neutrophil extracellular traps (NETs) towards the hypercoagulable state in IBD. We demonstrated that the levels of PS exposed MPs and the sources of MP-origin, platelets, erythrocytes, leukocytes and cultured endothelial cells (ECs) were higher in IBD groups than in healthy controls using flow cytometry and confocal mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(27 citation statements)
references
References 61 publications
0
26
0
1
Order By: Relevance
“…Recently, it has been demonstrated that neutrophils from IBD patients release more NETs than controls [149]. The authors propose that NETs, and also the elevated phosphatidylserine (PS) exposure on MPs from different cell origins, could be the link between IBD and the hypercoagulable state observed in these conditions.…”
Section: Contribution Of Neutrophils To Ibd-associated Thrombo-embmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it has been demonstrated that neutrophils from IBD patients release more NETs than controls [149]. The authors propose that NETs, and also the elevated phosphatidylserine (PS) exposure on MPs from different cell origins, could be the link between IBD and the hypercoagulable state observed in these conditions.…”
Section: Contribution Of Neutrophils To Ibd-associated Thrombo-embmentioning
confidence: 99%
“…ANCAs can indeed be directed against NET components, such as MPO, NE, cathespin G or proteinase 3. Thus, as also observed in systemic lupus erythematous (SLE), ANCAs may trigger the release of NETs from neutrophils and participate in the amplification of ANCA generation by exposing new antigenic proteins [149,151]. …”
Section: Contribution Of Neutrophils To Ibd-associated Thrombo-embmentioning
confidence: 99%
“…The role of MP in promoting NETosis was also demonstrated in a paper focusing on preeclampsia, in which placenta syncytiotrophoblast-derived MP seem to promote NETosis (117). In inflammatory bowel disease, MP also appear to activate NETosis (118). …”
Section: Microparticlesmentioning
confidence: 99%
“…Cells of the hematopoietic system, including neutrophils, platelets, and monocytes, have a major role in this process (64). There is increasing evidence implicating NET release with the development of both vein and arterial thrombosis (12, 14, 16, 26, 65, 7077). Extracellular deposition of DNA co-localized with neutrophil granule proteins has been shown in thrombi from patients with deep vein thrombosis (DVT) (78), especially at the phase of organization of the thrombus (70).…”
Section: Can Net Cargo Define Neutrophil Role In Disease?mentioning
confidence: 99%
“…Besides their role in infectious disorders, studies carried out after 2008 support the role of NETs in the pathophysiology of non-infectious diseases, such as thrombosis (1216), autoimmune diseases (14, 1722), genetically driven autoinflammatory (23), and other inflammation-related diseases (2426), metabolic disorders (27, 28), lung diseases (2932), fibrosis (33), and cancer (3436). …”
Section: Introductionmentioning
confidence: 99%